Value of medical genetic consultation at digestive organs diseases - T. V. Filippova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss value of medical genetic consultation at diseases of gastro-intestinal tract (GIT).Key points. The analysis of frequent hereditary gastroenterological diseases diagnosed with participation of doctor - geneticist. The role of hereditary factors in manifestation of monogenic and multifactorial diseases of a GIT is demonstrated. Value of modern molecular genetic technologies for detection of early stages of gastroenterological diseases is proved. General indications for medical genetic consultation for all gastrointestinal diseases are determined.Conclusion. Detection of disorders of functioning of various genes and duly medical genetic consultation allow to carry out early diagnostics, choose optimum mode of treatment and prevent diseases of GIT.